Reusing the urban fabric: adaptive re-use of an abandoned heritage building to explore community empowerment within the Johannesburg CBD's textile industry - Soobramoney, Kyle (University of the Witwatersrand, Johannesburg, 2023)
The city of Johannesburg has undergone massive transformations since its conception and the discovery of gold that set the city on an exponentially rising trajectory. In the aftermaths of apartheid, many post-industrial buildings are scattered through the city landscape, forgotten, and decaying with accompanying detrimental effects to their surrounding context. This investigation aims to reuse a delipidated heritage building to grow economy through local industry. In the case of this investigation, the relevant industry is the ever-growing textile and secondhand clothing market. This industry is contextually relevant, and the basic design principles of Architectural theory demand a building be responsive to the context to be successful. The hypothesis is that if an industrial function can be retrofitted to dilapidated buildings, then these buildings can be saved and enhance the environment in which it dwells. The textile industry in this case offers a multitude of job opportunities as well as applications in architecture and construction. Traits that could possibly help working class, and female entrepreneurs have a stronger foothold in the city, as industrial labor, and basic job access can become more available to women that may be unemployed and unskilled. Design methodologies such as adaptive re-use and symbiotic architecture are aimed to be implemented to endorse an architecture that is feasible for abandoned heritage buildings, concurrently these methodologies are intended to be explored through the textile industry. Architecture that is intended to be easy and cheap to assemble; architecture that can move, grow and change based on the needs of the user while preserving the identity of the building and at the same time creating a new one for a new generation. The end goal is to create a mixed use closed loop self-sustaining building that programmatically focuses on the education and economic components of the context as well as enhances community development in the city. The investigation aims to understand (through experimentation) if an architecture can be applied to the delipidating heritage typology as an effort to reuse space and the preserve character, memory, and diversity in a way that the generation of today will be excited to be in an old building. The city has become a hub for informal traders and entrepreneurs, a social and economic melting pot. There is an opportunity for existing industries to revitalize fragmented infrastructure to add to the mixture.
A research report submitted in partial fulfilment of the requirements for the degree Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2023
Keywords: Heritage building; Textile industry; Symbiotic architecture; UCTD